Young artists in Italy at the turn of the millenium : Behind and beyond the Italian Studio Program at P.S.1 / MoMA - Bertola, Chiara; Cerizza, Luca; Cherubini, Laura; Codognato, Mario; Daolio, Roberto; Esposito, Bruna; Galasso, Alessandra; Garutti, Alberto; Gropello, Giulio di; Mezzaqui, Sabrina; Ontani, Luigi; Pagano di Melito, Andrea; et al. (Long Island Milano : Edizioni Charta Milano P.S.1 Contemporary Art Center Long Island, 2005)
Andrini, Alessandra ; Bartolini, Massimo ; Benassi, Elisabetta ; Berti, Simone ; Bertocchi, Davide ; brigataes ; Caravaggio, Gianni ; Ceresoli, Alessandro ; Chiasera, Paolo ; Esposito, Bruna ; Fantin, Emilio ; Favaretto, Lara ; Galegati, Stefania ; Gennari, Francesco ; Grimaldi, Massimo ; Jeane, Norma ; Ligorio, Deborah ; Losi, Claudia ; Maggio, Elisabetta di ; Mala.Arti Visive ; Maloberti, Marcello ; Marisaldi, Eva ; Mezzaqui, Sabrina ; Mocellin, Ottonella ; Nicoletta, Sandrine ; Norese, Giancarlo ; Pagliarini, Arpiani ; Perrone, Diego ; Piccioni, Roberta ; Pivi, Paola ; Previdi, Riccardo ; Puppi, Daniele ; Rivola, Fabrizio ; Rizzo, Luigi ; Rossi, Sara ; Tesi, Alessandra ; Toderi, Grazia ; Torelli, Sabrina ; Tuttofuoco, Patrick ; Vedovamazzei ; Vitone, Luca ; Xhafa, Sislej ; Zuffi, Italo
biog., ind. tent., gr. tent. per kunstenaar [1 p.]
Engels
boek